Peran Orang Tua dan Guru dalam Membangun Karakter Anak di SD Kristen Shalom Semarang - Lidiawati Lidiawati; Lucky Antonio; Matius Kala'tiku; Anita Mariana Parulian Butar-Butar; Chanita Christie (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
The rapid advancement of technology has had a significant impact on children's lives, with many opting to play and learn through digital devices like smartphones and computers. This trend potentially hinders their character development, particularly due to reduced interaction with parents and teachers. Character education, which should be a fundamental part of children's growth, is often neglected due to the negative influences of technology. This study aims to analyze the role of parents and teachers in character education for children in the digital era and its effects on moral development. The research employs a qualitative approach, utilizing literature review and interviews with parents and teachers. The state of the art in this research refers to Lawrence Kohlberg's moral development theory, which explains how children understand moral rules according to their age. The novelty of this study lies in emphasizing the importance of collaboration between parents and teachers in nurturing children's character while avoiding authoritarian approaches that may hinder their development. The results indicate that active involvement from both parents and teachers is crucial in shaping children's character, and consistent guidance is needed to address the challenges posed by digital development. In conclusion, a balanced character education that integrates digital exposure with moral values is essential in shaping a generation with integrity and maturity.